2014
DOI: 10.1039/c4ob00737a
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective synthesis of spiroacetals: the conquest of a long-sought goal in asymmetric catalysis

Abstract: This perspective article briefly outlines the very few and recent methods reported in the literature on catalytic asymmetric synthesis of spiroacetals from achiral substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…A large number of complex molecules with interesting biological activities present a spirocyclic core. In the recent years a growing interest in building such core has led to numerous reports on the synthesis of spirocyclic derivatives such as spiroacetals, 1 spirolactams, [2][3][4][5][6][7] spirolactones, 8 spirooxindoles, 9,10 spiroindolones, 11 and spirocyclanes 12 just to name a few. Spirocyclohexadienones are an important class of precursors for the construction of such complex structures.…”
mentioning
confidence: 99%
“…A large number of complex molecules with interesting biological activities present a spirocyclic core. In the recent years a growing interest in building such core has led to numerous reports on the synthesis of spirocyclic derivatives such as spiroacetals, 1 spirolactams, [2][3][4][5][6][7] spirolactones, 8 spirooxindoles, 9,10 spiroindolones, 11 and spirocyclanes 12 just to name a few. Spirocyclohexadienones are an important class of precursors for the construction of such complex structures.…”
mentioning
confidence: 99%
“…First, in 1983 it was synthesized by two independent groups [26,27]. Numerous studies have been reported in the literature thereafter concerning the synthesis of pheromone including asymmetric synthesis [28]. Kranidiotis et al [24] proposed a novel short synthesis of racemic 1,7-dioxaspiro [5.5]undecane, named (±)-olean (Figure 1), through cross metathesis resulting in a cheap and easy to follow procedure.…”
Section: Synthesis and Characterization Of Dacus Pheromonementioning
confidence: 99%
“…Although many synthetic approaches towards olean syntheses have been reported in literature, including their asymmetric syntheses [28], we decided to developed a new simple and efficient synthesis of olean in five steps, starting from butane-1,4-diol, as outlined in Scheme 1. Although many synthetic approaches towards olean syntheses have been reported in literature, including their asymmetric syntheses [28], we decided to developed a new simple and efficient synthesis of olean in five steps, starting from butane-1,4-diol, as outlined in Scheme 1. Firstly, butane-1,4-diol was monobenzylated using benzyl bromide as limiting reagent in 99% yield (based on benzyl bromide).…”
Section: Characterization Of Prepared Microparticlesmentioning
confidence: 99%
“…Chiral O , O ‐acetals and ketals are prevalent in many natural products and pharmaceuticals and a wide range of bioactivities are associated with them Thus a large number of synthetic research groups are engaged in the asymmetric synthesis of these compounds . A number of valuable approaches has been reported for the synthesis of mono cyclic acetals, fused acetals and spiroketals .…”
Section: Introductionmentioning
confidence: 99%